Peran Media Sosial dalam Mendorong Kesadaran Kesetaraan Gender di Kalangan Generasi Muda - Alfira Khoirunnisa; Hisny Fajrussalam; Nadhira Aulia Hermawan; Salsyabilla Putri Laelany; Tiara Naswa Sari; Cheppy Risnandar Angga Widjaya (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2025)
This research aims to describe gender equality based on humanity, justice and religion, where men and women must be equal and there should be no difference or more dominant. By utilizing the role of social media, it can be a space for dialogue for gender issues, strengthen the equality movement, and also shape public opinion because the role of social media allows the dissemination of educational messages to encourage critical understanding of the roles of men and women among the younger generation. The method used is a literature study/literature study with a content analysis-based analysis approach that examines the results of research on scientific articles, books, verse fragments in the Qur'an and also ebooks. The results of the study show that gender equality among the younger generation is related to the role of social media as a tool for disseminating information, making it easier to spread gender understanding. In line with the process, the challenge faced from the dissemination of information through social media is the lack of critical thinking to filter incoming information.